Representasi Al-Khamr Dalam Al-Qur’an (Studi Semiotika Roland Barthes) - Mawardi Khalid; Normuslim; Ahmadi (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
Al-Khamr is one of the Arabic words found in the Qu’'an that gives a variety of interpretations because it is a term that refers to the nature of a thing. Many Islamic scholars of the past and present provide different understandings based on context and concept. This different understanding has an impact on the legal derivatives of khamr itself. This article tries to examine slowly using the theory of signs and grammar so as to produce basic concepts and applied concepts. Resulting in an understanding that khamr is not only a drink resulting from processed or fermented wine and so on. Understanding Khamr can be an object or a condition both environment and system that has caused the closing of the mind so that humans as intelligent beings can no longer think in their nature. Keywords: Al-Khamr, Representation, Quran, Semiotics, Roland Barthes